Functional neurological disorders in Parkinson disease - Wissel, Benjamin; Balint, Bettina (Journal of neurology, neurosurgery, and psychiatry, 2018)
Objective: To ascertain demographic and clinical features of Parkinson disease (PD) associated with functional neurological features. - Methods: A standardised form was used to extract data from electronic records of 53 PD patients with associated functional neurological disorders (PD-FND) across eight movement disorders centres in the USA, Canada and Europe. These subjects were matched for age, gender and disease duration to PD patients without functional features (PD-only). Logistic regression analysis was used to compare both groups after adjusting for clustering effect. - Results: Functional symptoms preceded or co-occurred with PD onset in 34% of cases, nearly always in the most affected body side. Compared with PD-only subjects, PD-FND were predominantly female (68%), had longer delay to PD diagnosis, greater prevalence of dyskinesia (42% vs 18%; P=0.023), worse depression and anxiety (P=0.033 and 0.025, respectively), higher levodopa-equivalent daily dose (972±701 vs 741±559 mg; P=0.029) and lower motor severity (P=0.019). These patients also exhibited greater healthcare resource utilisation, higher use of [(123)I]FP-CIT SPECT and were more likely to have had a pre-existing psychiatric disorder (P=0.008) and family history of PD (P=0.036). - Conclusions: A subtype of PD with functional neurological features is familial in one-fourth of cases and associated with more psychiatric than motor disability and greater use of diagnostic and healthcare resources than those without functional features. Functional manifestations may be prodromal to PD in one-third of patients.
Gesehen am 01.04.2020